Antioxidant Properties and Cardioprotective Mechanism of Malaysian Propolis in Rats - Ahmed, Romana; Tanvir, E. M.; Hossen, Md. Sakib; Afroz, Rizwana; Ahmmed, Istiyak; Rumpa, Nur-E-Noushin; Paul, Sudip; Siew, Hua Gan; Sulaiman, Siti Amrah; Khalil, Md. Ibrahim (Hindawi Publishing Corporation, 2017)
Propolis contains high concentrations of polyphenols, flavonoids, tannins, ascorbic acid, and reducing sugars and proteins. Malaysian Propolis (MP) has been reported to exhibit high 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity and ferric reducing antioxidant power (FRAP) values. Herein, we report the antioxidant properties and cardioprotective properties of MP in isoproterenol- (ISO-) inducedmyocardial infarction in rats.MaleWistar rats (